Strategies of Social Reproduction of Family Farmers in the Border Region of Cerro Largo, Uruguay - González Ruiz, Jimena; Sacco Dos Anjos, Flávio (Agrociencia Uruguay, 2015)
This paper analyses the dynamics of family farming in Cerro Largo, Uruguay, especially in the borderline region with Brazil, through the study of the social, economic and cultural organization of the family production units. The emphasis is on the social reproduction strategies of these family farmers. The research fits into a border social context, signed by the consequences of modernization of the productive structure of the country. Among the consequences of the agricultural policies applied from the 1970´s in Uruguay, there is an increasing concentration of the the land and the means of production, and a sharp fall of the number of family farmers. Uruguayan agro currently experiments the emergence of a new business sector, linked mainly to forest crops and rainfed agriculture, with a strong presence of foreign capital. This new entrepreneurship is into the context of the traditional, fundamentally linked to livestock production. Meanwhile, a set of family farms remain active and resist their complete disappearance. Some of the diverse strategies that the family farmers use to remain living and producing in the countryside are: the exercise of pluriactivity, the practice of self-consumption, the economic benefits of the residence on the border with Brazil, and government financial transfers.